The Influence Of Work Ethic And Organizational Justice On The Organizational Commitment Of Civil Servants Of The Office Of Women Empowerment And Child Protection Of West Kalimantan Province - Resa Dintiah; Irfan Mahdi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to examine the influence of work ethics and organizational justice on the organizational commitment of civil servants in the Department of women's empowerment and Child Protection of West Kalimantan province. This study uses an associative approach with saturated sampling techniques. The sample consisted of 34 employees working in the Inspectorate Kubu Raya. Data analysis was conducted using multiple linear regression analysis with SPSS software version 25. The tests conducted in this study include validity test, reliability test, normality test, linearity test, and multicollinearity test. Hypothesis testing is done by using simultaneous test (F test) and Partial Test (t test). Based on the results of hypothesis testing, both simultaneously (F test) and partially (t test), it can be concluded that together work ethics and organizational justice have a positive and significant influence on organizational commitment. However, individual work ethic has no significant effect on organizational commitment, while organizational justice has been shown to have a significant effect on such commitment.